Guidelines for Qualifications of Neurodiagnostic Personnel: A Joint Position Statement of the American Clinical Neurophysiology Society, the American Association of Neuromuscular & Electrodiagnostic Medicine, the American Society of Neurophysiological Monitoring, and ASET – The Neurodiagnostic Society. (2nd January 2023) - López, Jaime R.; Ahn-Ewing, Judy; Emerson, Ron; Ford, Carrie; Gale, Clare; Gertsch, Jeffery H.; Hewitt, Lillian; Husain, Aatif; Kelly, Linda; Kincaid, John; Kise, Meledy; Kornegay, Adam; et al.
ABSTRACT: The Guidelines for Qualifications of Neurodiagnostic Personnel (QNP) document has been created through the collaboration of the American Clinical Neurophysiology Society (ACNS), the American Society of Neurophysiological Monitoring (ASNM), the American Association of Neuromuscular & Electrodiagnostic Medicine (AANEM), and ASET – The Neurodiagnostic Society (ASET). The quality of patient care is optimized when neurophysiological procedures are performed and interpreted by appropriately trained and qualified practitioners at every level. These Societies recognize that Neurodiagnostics is a large field with practitioners who have entered the field through a variety of training paths. This document suggests job titles, associated job responsibilities, and the recommended levels of education, certification, experience, and ongoing education appropriate for each job. This is important because of the growth and development of standardized training programs, board certifications, and continuing education in recent years. This document matches training, education, and credentials to the various tasks required for performing and interpreting Neurodiagnostic procedures. This document does not intend to restrict the practice of those already working in Neurodiagnostics. It represents recommendations of these Societies with the understanding that federal, state, and local regulations, as well as individual hospital bylaws, supersede these recommendations. As Neurodiagnostics is a growing and dynamic field, we fully intend this document to change over time.